(3OjhGf GdGSdGes - (3GdZRj , eMeO Hf YHO GdQMef Hf Rjf GdYGHOjf GdYGeQj, TeS GdOjf CHh GdeYGdj,J (B1167 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCMO GdhGMO s
(3BNQgG (B:s
(3Je hced hGdMeO ddg QH GdYGdejf s
(3eQJHkG Ydi GdMQhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B140s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B135 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B1154) s
Keywords: (3GdJGQjNs